How countries become rich and reduce poverty: A review of heterodox explanations of economic development - Lindsay Whitfield (Danish Institute for International Studies (DIIS), 2011)
For the sake of less developed countries, it is time to adjust the discourses of international development assistance on poverty reduction. This article attempts to do so by reviewing new and old literature explaining why some countries are rich and others are poor. History has repeatedly shown that the single most important thing that distinguished rich countries from poor ones is basically their higher capabilities in manufacturing. We have to shift the discussion about ending world poverty back to one about structural transformation of the economy and increasing technological capabilities.
Keywords: 330; Armut; Entwicklung; Systemtransformation; Entwicklungsländer